2006
DOI: 10.1128/aac.50.2.731-738.2006
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Evolution of Ceftazidime Resistance in Extended-Spectrum β-Lactamase CTX-M-9

Abstract: A random mutagenesis technique was used to predict the evolutionary potential of ␤-lactamase CTX-M-9 toward the acquisition of improved catalytic activity against ceftazidime. Thirty CTX-M mutants were obtained during three rounds of mutagenesis. These mutants conferred 1-to 128-fold-higher MICs of ceftazidime than the parental enzyme CTX-M-9. The CTX-M mutants contained one to six amino acid substitutions. Mutants harbored the substitutions Asp240Gly and Pro167Ser, which were previously observed in clinical C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 41 publications
(45 reference statements)
1
29
0
1
Order By: Relevance
“…Mutation at codon 167 resulted in Glycine ? Arginine substitution in the constituent omega loop (161 to 179 codon), situated at the floor of catalytic active site of CTX-M enzyme [26]. Both codons 242 and 259 encode amino acids constituent of a/b domain of CTX-M protein.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation at codon 167 resulted in Glycine ? Arginine substitution in the constituent omega loop (161 to 179 codon), situated at the floor of catalytic active site of CTX-M enzyme [26]. Both codons 242 and 259 encode amino acids constituent of a/b domain of CTX-M protein.…”
Section: Discussionmentioning
confidence: 99%
“…coli BL21(DE3) cells (Novagen) containing the pET 9a (ϩ) expression vector were grown in superoptimal broth (SOB) containing 50 g/ml kanamycin (11,16). These cells were grown with agitation at 37°C until an optical density at 600 nm of 0.8 was attained.…”
Section: Methodsmentioning
confidence: 99%
“…The bla CTX-M-9 gene was cloned into the pET9a (ϩ) plasmid vector (Novagen) as described previously and was maintained in E. coli BL21(DE3) cells (11,16).…”
Section: Methodsmentioning
confidence: 99%
“…This mutation is found in the naturally occurring enzymes of the CTX-M-2 and CTX-M-9 clusters (CTX-M-35 and CTX-M-19) and, as shown by Welsh et al (30), can be readily selected with CAZ following the in vitro mutagenesis of CTX-M-2. It is interesting to note that our in vitro experiments as well as similar studies by other authors (10,19,24,30) yielded only the Pro3Ser mutation at position 167, whereas a variety of substitutions at this position have been found in the naturally occurring CTX-M ceftazidimases (e.g., Thr in CTX-M-23 and CTX-M-42, Ser in CTX-M-52, and Gln in CTX-M-54). Although the reason for this remains unclear, it may be at least partially explained by the fact that a nucleotide transition required for the Pro167Ser substitution is more likely to occur in almost all types of mutators, including the mutD5 strain used in our experiments and the mutS strains employed in the other studies (19,24).…”
Section: Resultsmentioning
confidence: 80%
“…Recently, however, several CTX-M variants have been reported to contain point mutations at amino acid position 167 or 240 (Ambler's numbering scheme [1]) in association with increased CAZ-hydrolyzing activity, which leads to a higher level of CAZ resistance (2,3,5,8,21,22,25,27,28). Substitutions of these amino acids in CTX-M enzymes have been shown in both clinical isolates (3,8,25,28) and mutants selected in vitro by CAZ exposure (10,22,24,30). In recent studies by Karisik et al (19) and Novais et al (24), it has been demonstrated that mutations at position 167 in CTX-M-3, which lead to increased CAZ resistance, are readily selected in vitro when mutator host strains are used.…”
mentioning
confidence: 99%